2017
DOI: 10.1189/jlb.3a0317-124r
|View full text |Cite
|
Sign up to set email alerts
|

Alpha1-antitrypsin binds hemin and prevents oxidative activation of human neutrophils: putative pathophysiological significance

Abstract: Heme is a ubiquitous compound of human tissues, and it is involved in cellular physiology and metabolism. Once released from the cell, free heme oxidizes to the ferric state (hemin). High levels of hemin can cause oxidative stress and inflammation if not neutralized immediately by specialized scavenger proteins. Human alpha1-antitrypsin (A1AT), an acute-phase glycoprotein and important inhibitor of neutrophil proteases, is also a hemin-binding protein. A short-term exposure of freshly isolated human blood neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…In turn, phosphorylation of the head domain at S72 has been shown to associate with vimentin recruitment to the cell surface upon treatment with N-acetyl-glucosamine (N-AcGln) polymers [49], thus strengthening the importance of PTM for vimentin exposure. Interestingly, extracellular exposure of the protein is frequently associated with oxidative stress [42]. Consistent with this, oxidative modifications and electrophile addition have also been reported on extracellular vimentin [33].…”
Section: Extracellular Vimentinsupporting
confidence: 64%
See 1 more Smart Citation
“…In turn, phosphorylation of the head domain at S72 has been shown to associate with vimentin recruitment to the cell surface upon treatment with N-acetyl-glucosamine (N-AcGln) polymers [49], thus strengthening the importance of PTM for vimentin exposure. Interestingly, extracellular exposure of the protein is frequently associated with oxidative stress [42]. Consistent with this, oxidative modifications and electrophile addition have also been reported on extracellular vimentin [33].…”
Section: Extracellular Vimentinsupporting
confidence: 64%
“…Vimentin can be exposed at the surface or secreted by several cell types, including activated macrophages [14] and neutrophils [42], endothelial cells (HUVEC and brain microvascular endothelial cells) [43,44], and platelets [45]. Extracellular vimentin has been involved in a variety of processes, including cell-cell interaction, hemostasis, immune activation, interaction with pathogens and tissue repair (see below).…”
Section: Extracellular Vimentinmentioning
confidence: 99%
“…Hemoglobin-derived free heme is a cytotoxic molecule that mediates oxidative stress, cell activation, and amplifies inflammatory responses. Our in vitro data provide novel evidence that AAT, as a free heme scavenger, markedly reduces or abolishes the neutrophil-activating effects of heme including neutrophil spreading, surface expression of vimentin, ROS production, and release of IL-8, and neutrophil adhesion to human endothelial cells ( Janciauskiene et al, 2017 ). It is important to point out that the oxidized form of AAT (without anti-elastase activity), still binds heme.…”
Section: Role Of Aat Beyond Inhibition Of Neutrophil Proteasesmentioning
confidence: 79%
“…Notably, albumin is a negative acute phase protein in humans and it is conceivable that during severe inflammatory conditions, when the heme-neutralizing capacity of albumin decreases, other acute-phase proteins such as AAT will participate. AAT is a HBP with binding affinity similar to albumin ( 59 ) and it has previously been demonstrated that AAT markedly reduces free heme neutrophil-activating effects, including the production of ROS ( 63 ). Serum HBPs not only bind and neutralize free heme with different binding affinities, but may also acquire novel biological activities via specific interactions with heme ( 64 – 66 ).…”
Section: Heme Interactions With Serum Heme-binding Proteins and Role mentioning
confidence: 99%